Pseudoclass iii and class iii skeletal patients, with maxillary ectopic teeth, from ages 8 to 18, from the Center for Advanced Orthodontic Studies (ceso), unam (Revista Nacional de Odontología, 2018)
Introduction: Associations between different dental anomalies are not considered important from anetiological point of view. However, these are relevant from a clinical point of view since early diagnosisof an anomaly may indicate a high risk of appearance for others. Objective: To determine the presence of ectopic upper pseudoclass iii and skeletal class iii teeth in patients ranging from 8 to 18 years old, by means of Bolton’s analysis in the lateral cranial and panoramicradiographs. Methodology: A descriptive, cross-sectional and observational study. Work is done with cephalic radio-graphs; the lengths and distance of the anterior nasal spine were compared by overlaying the palatalvault using Bolton templates. The superimposition of Bolton standards according to age was alsoconducted. Results: The presence of ectopic canine teeth is frequent in women; left and right ones in 37%, fol-lowed by the central incisors and the right lateral incisor. 78% of tooth retention is unilateral. Conclusions: There may be a relationship between class iii and skeletal pseudoclass iii with maxillaryhypoplasia, as well as with the presence of ectopic teeth in the upper anterior sector.
Keywords: upper ectopic maxillary canine teeth; skeletal; pseudoclass iii